Characterization of the Delamination Defects in Marine Steel Using Laser-Induced Breakdown Spectroscopy *supported by a Special Fund for Nationally Important Instruments of China (No. 2012YQ20018208). (August 2015) - Yang, Chun; Jia, Yunhai; Zhang, Yong; Li, Dongling; Liu, Jia; Chen, Jiwen; Chen, Yongyan; Liu, Ying
Abstract In this paper, two types of comparison analyses, bulk analysis and defect analysis, were carried out for marine steel. The results of laser-induced breakdown spectroscopy (LIBS) were compared with those of spark optical emission spectrometry (Spark-OES) and scanning electron microscopy/energy dispersion spectroscopy (SEM/EDS) in the bulk and defect analyses. The comparison of the bulk analyses shows that the chemical contents of C, Si, Mn, P, S and Cr obtained from LIBS agree well with those determined using Spark-OES. The LIBS is slightly less precise than Spark-OES. Defects were characterized in the two-dimensional distribution analysis mode for Al, Mg, Ca, Si and other elements. Both the LIBS and SEM/EDS results show the enrichment of Al, Mg, Ca and Si at the defect position and the two methods agree well with each other. SEM/EDS cannot provide information about the difference in the chemical constituents when the differences between the defect position and the normal position are not significant. However, LIBS can provide this information, meaning that the sensitivity of LIBS is higher than that of SEM/EDS. LIBS can be used to rapidly characterize marine steel defects and provide guidance for improving metallurgical processes.